Study of the possibility of increasing the probing depth by the method of reflection confocal microscopy upon immersion clearing of near-surface human skin layers. - Meglinski, I. V.; Bashkatov, A. N.; Genina, E. A.; Churmakov, D. Y.; Tuchin, V. V. (Turpion Ltd., 2002)
The possibility of increasing the human-skin probing depth by the method of reflection confocal microscopy (RCM) upon decreasing the amplitude of spatial fluctuations of the refractive index of the upper skin layers is considered. A change in the probing depth is estimated by analysing the spatial distribution of the probability density of the effective optical paths of detected photons calculated by the Monte Carlo method. The results of the numerical simulation are interpreted within the framework of the possible application of RCM to the study of the human skin exposed to an immersion liquid compatible to it. A diffusion of the immersion agent into the skin depth involves the equalising of the refractive indices of the structural elements of near-surface skin layers, which in turn causes a decrease in the scattering intensity and a certain increase in the transparency of the upper tissue layers. It is shown that a decrease in the light scattering in the near-surface skin layers leads to a significant increase in the probing depth obtained with the RCM technique.